Aplicación de citokinina para floración en arboles de guayaba - Merchan Espinoza, Gonzalo Fabrizzio (2008)
In the farm Santa Inés of the Technical University of Machala, you to study them effects taken place by the pruning accompanied by aspersions of a fitohormonas citokinina in trees longevos, with the purpose of counting new experiences in the employment of new agricultural inputs with the help of fitohormonas. The outlined objectives were. • To evaluate the effect of the citokinina application in trees of guava longevos. • To determine the most appropriate dose for the emission of buds and flowers of the guava. • To settle down alternative of handling of the guava under the conditions of the means. One works with three doses of powdered formulated citokin you wet him, these were 200, 500 and 800 ml for plant, applied in aspersion to the shafts and the floor so that they are absorbed by the system radicular. The application one carries out with a team of conventional aspersion. In the orchard of fruit-bearing of the Farm in mention was selected 12 trees, to which are assigned the czar one of the four treatments, in such a way that you organizes a Design at random in Blocks with three reply, being counted 12 trees in the whole rehearsal. For the taking of data, of each tree you registration the information in four branches, guided in sense of the geographical points and each branch, you registration forty floral bearings, that which I represent 20% of the potential production of a mature plant calculably. The studied variables were: Growth of the buds until the 43 days, I number of floral bearings, Number of flowers for bearing, Number of fruits for bearings, Size of the fruits (long and diameter), I weigh of the fruits. The variance analyses for the longitude of the buds gave high statistical significance, demonstrating that the growth in the period of observation was adjusted a model of lineal growth with a rate that was superior that the absolute witness. He numbers of bearings, flowers and fruits for bearing they were superior that the witness and among dose of Citokin it didn't exist significant deferences, I didn't seize in the production of fruits for branch, it plants statistically in which the low dose of 20 ml/ha of Citokin was superior that the half, and high doses The increments in the production of fruits with regard to the witness overcame 100%.